Knowledge and beliefs on child sexual abuse by Spanish university students - Pereda, Noemí; Arch, Mila; Guerra-González, Raquel; Llerena, Gemma; Berta-Alemany, Marta; Saccinto, Elisa; Gascón, Ester (Anales de Psicología / Annals of Psychology, 2012)
Objective: The aim of this study was two-fold: to assess the level of knowledge of a sample of Spanish university students about child sexual abuse and to analyze the beliefs and myths that the university population has concerning this kind of maltreatment. Method: A random sample (n = 200) of students enrolled in Psychology were surveyed with a 21 items questionnaire. Results: The students stated that sexual abuse can occur at any age (61.3%) and in both sexes (58.8%). Besides, they place these acts within the family context (86.9%). However, just the 13% of the students have some knowledge about assessment methods of child sexual abuse and the majority of them do not know its criminal consequences (73.9%). If they had the certainty that an abuse has occurred, 98.5% would report it to the authorities; nevertheless, if they had just suspected it, an 81.3% of them would not report the alleged abuse. Conclusions: The results obtained show that the students surveyed had a good knowledge regarding child sexual abuse. However, there are still false beliefs which can impair the proper development of the profession.